A Neuroscience-Based Model for Developing Religious Moderation: The Perspective of Muhammadiyah Ulama’s Living Fatwas During the Covid-19 Pandemic in Indonesia - Mohammad Jailani (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2025)
The Covid-19 pandemic has created new dynamics in religious practice, particularly in the tension between spirituality and adherence to health protocols. Lockdown policies that restricted public worship activities, such as the closure of mosques and prayer rooms, triggered various responses, including the narrative “fearing hell more than Covid-19.” This article argues that the development of moderate religious attitudes can be conceptually constructed through integrating neuroscience perspectives with the living fatwa of Muhammadiyah scholars during the pandemic. This study employs a qualitative literature-based approach, drawing on key sources concerning religious moderation, Muhammadiyah fatwas related to Covid-19, and relevant literature on neuroscience in Islamic education. Data were analyzed using content analysis methods that emphasize intertextuality and conceptual articulation. The findings indicate that a moderate religious attitude is not merely normative-theological but is also closely linked to cognitive and affective processes in the human brain, as reflected in the practice of living Islam. This study reinforces the importance of fatwas as both an ethical reference and a subject of critical analysis through neuroscience within contemporary Islamic studies. The article contributes to broadening the academic framework of religious moderation through an interdisciplinary approach between Islamic studies and neuroscience.